Criticism of Sanad Hadith in DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017 on the Mudharabah Contract - Purwantoro (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2025)
Background. The fatwa of the National Sharia Council–Indonesian Ulema Council (DSN-MUI) serves as a bridge between Islamic legal principles and modern financial practices in Indonesia, including in the regulation of mudharabah contracts through DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017. This fatwa is based on the Qur’an, hadith, and ijtihad of scholars as its normative basis. However, the quality of the hadith referred to has not been comprehensively explained, even though its validity is highly dependent on the takhrij process which includes source tracing, analysis of sanad and matan, and determination of the hadith’s degree according to the rules of hadith science. Aim. This study aims to analyze the quality of the hadiths used in DSN-MUI Fatwa No. 115/DSN-MUI/IX/2017 concerning Mudharabah Contracts through the hadith takhrij approach. Methods. This research is a qualitative study using library research methods. Data sources include the main books of hadith (kutub al-tis’ah), books of hadith commentary, and rijal al-hadith literature. The research process is carried out through identification of hadith in fatwas, tracing of narration sources in lafzi and ma’nawi, analysis of the continuity of the sanad (ittishal al-sanad), evaluation of the credibility of narrators based on jarh wa ta’dil, and assessment of the quality of hadith from the sanad aspect to determine its degree (sahih, hasan, or da’if). Results. The hadith used in the fatwa does not yet have a completely authentic level. So it is still necessary to search for supporting hadiths of authentic quality.